Measuring Critical Care Providers' Attitudes About Controlled Donation After Circulatory Death. (June 2018) - Rodrigue, James R.; Luskin, Richard; Nelson, Helen; Glazier, Alexandra; Henderson, Galen V.; Delmonico, Francis L.
Introduction: Unfavorable attitudes and insufficient knowledge about donation after cardiac death among critical care providers can have important consequences for the appropriate identification of potential donors, consistent implementation of donation after cardiac death policies, and relative strength of support for this type of donation. The lack of reliable and valid assessment measures has hampered research to capture providers' attitudes. Design and Research Aims: Using stakeholder engagement and an iterative process, we developed a questionnaire to measure attitudes of donation after cardiac death in critical care providers (n = 112) and examined its psychometric properties. Exploratory factor analysis, internal consistency, and validity analyses were conducted to examine the measure. Results: A 34-item questionnaire consisting of 4 factors (Personal Comfort, Process Satisfaction, Family Comfort, and System Trust) provided the most parsimonious fit. Internal consistency was acceptable for each of the subscales and the total questionnaire (Cronbach α > .70). A strong association between more favorable attitudes overall and knowledge ( r = .43, P < .001) provides evidence of convergent validity. Multivariable regression analyses showed that white race ( P = .002) and more experience with donation after cardiac death ( P < .001) were significant predictors of more favorable attitudes. Conclusion: Study findings support the utility, reliability, and validity of a questionnaire for measuring attitudes in critical care providers and for isolating targets for additional education on donation after cardiac death.